2009
DOI: 10.1063/1.3265955
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-energy correlations in liquids. III. Statistical mechanics and thermodynamics of liquids with hidden scale invariance

Abstract: In this third paper of the series, which started with Bailey et al. ͓J. Chem. Phys. 129, 184507 ͑2008͒; ibid. 129, 184508 ͑2008͔͒, we continue the development of the theoretical understanding of strongly correlating liquids-those whose instantaneous potential energy and virial are more than 90% correlated in their thermal equilibrium fluctuations at constant volume. The existence of such liquids was detailed in previous work, which identified them, based on computer simulations, as a large class of liquids, in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
157
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(165 citation statements)
references
References 55 publications
5
157
3
Order By: Relevance
“…Thus systems interacting via the LJ potential inherit strong WU correlations from an underlying inverse power-law-they have a "hidden scale invariance." 3,28 Paper III 3 gave further numerical evidence for the explanation for strong WU correlations presented in Paper II, and theoretical results were given on the statistical mechanics and thermodynamics of the hidden scale invariance that characterizes strongly correlating liquids. It was also shown that strong virial potential-energy correlations are present even in out-ofequilibrium situations-the hidden scale invariance is a property of the potential energy surface, not just of the equilibrium states.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Thus systems interacting via the LJ potential inherit strong WU correlations from an underlying inverse power-law-they have a "hidden scale invariance." 3,28 Paper III 3 gave further numerical evidence for the explanation for strong WU correlations presented in Paper II, and theoretical results were given on the statistical mechanics and thermodynamics of the hidden scale invariance that characterizes strongly correlating liquids. It was also shown that strong virial potential-energy correlations are present even in out-ofequilibrium situations-the hidden scale invariance is a property of the potential energy surface, not just of the equilibrium states.…”
Section: Introductionmentioning
confidence: 87%
“…This is the final paper in a series [1][2][3][4] investigating the properties of strongly correlating liquids, 5 i.e., liquids that have strong correlations between their constant-volume equilibrium fluctuations of potential energy, U (t), and virial 6,7 W (t) ≡ −1/3 i r i · ∇ r i U (r 1 , ..., r N ) where r i is the position of particle i at time t. As is well known, the average virial W gives the configurational contribution to the pressure:…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The study of thermodynamic scaling has triggered the proposal of several novel concepts by Dyre and coworkers, such as that of "strongly correlating liquids" (i.e., liquids with strong correlations between equilibrium fluctuations of the potential energy and the virial in a canonical ensemble) and "isomorphs" (i.e., curves in the phase diagram along which structure, dynamics, and some thermodynamic properties are invariant in reduced units) . [23][24][25][26][27][28] The isomorph theory indicates that the scaling exponent γ is not constant, but depends on density, [27][28][29][30] and the power-law form ρ γ is only a special case. However, the power-law density scaling is a useful approximation to the isomorph scaling since a number of experiments find a weak dependence of γ on density under certain thermodynamic conditions [4][5][6] and since using a constant value of γ leads to collapse onto a master curve of the dynamics in glass-forming liquids.…”
Section: Introductionmentioning
confidence: 99%
“…According to the isomorph theory [7][8][9][10][11], the class of socalled strongly correlating liquids have isomorphs, which are curves in the phase diagram along which structural, dynamical, and some thermodynamic properties are invariant when expressed in reduced units. This theory has been tested successfully experimentally [12] and numerically [13][14][15].…”
Section: Introductionmentioning
confidence: 99%